This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given, x ∈ R . Now, the square root function is a bijection from R 0 + to R 0 + , i.e., the square root function generally returns positive value (including zero).
Now, if x is (+ve), then the value of x 2 = x .
If x is (-ve), then the value of x 2 = ( − x ) .
These two values can be collectively expressed by saying that x 2 = ∣ x ∣ .
Now, coming onto 3 x 3 , for all x ∈ R , we have 3 − x 3 = 3 ( − 1 ) × 3 x 3 = ( − 1 ) × x = ( − x ) .
So, the answers are ∣ x ∣ and ( − x ) respectively.
P.S. -- Sorry for the bad formatting! I am a little bad with LaTeX. :P